High-power narrow-linewidth blue external cavity diode laser. (April 2023) - Han, Jinliang; Zhang, Jun; Shan, Xiaonan; Peng, Hangyu; Zhang, Yawei; Qin, Li; Wang, Lijun
Highlights: A high efficiency spectral linewidth narrowing structure is proposed. A blue diode laser with 444.36 nm central wavelength and 0.18 nm spectral linewidth is achieved. The 40 W class narrow-linewidth blue diode laser is the highest reported to date. Abstract: An external cavity feedback structure based on volume Bragg grating is introduced to realise spectral stabilisation and linewidth narrowing of a blue diode laser, with a central wavelength of 444.36 nm and a spectral linewidth of 0.18 nm. Using spatial beam combining technology and fibre coupling technology, a blue diode laser source producing 40.3 W power from an output fibre (core diameter: 105 µm, numerical aperture: 0.22) is achieved at an operating current of 3 A. The external cavity feedback and fibre coupling efficiencies exceeded 101.8 % and 88 %, respectively. Such high-power narrow-linewidth blue diode lasers show potential applications in second-harmonic generation, high-resolution spectroscopy, medical treatment, and industrial processing. To the best of our knowledge, the 40 W class output power with the narrow-linewidth of a fibre-coupled blue diode laser is the highest reported to date.